Biaxial Strains Mediated Oxygen Reduction Electrocatalysis on Fenton Reaction Resistant L10‐PtZn Fuel Cell Cathode. Issue 29 (5th June 2020) - Liang, Jiashun; Zhao, Zhonglong; Li, Na; Wang, Xiaoming; Li, Shenzhou; Liu, Xuan; Wang, Tanyuan; Lu, Gang; Wang, Deli; Hwang, Bing‐Joe; Huang, Yunhui; Su, Dong; et al.
Abstract: PtM alloy catalysts (e.g., PtFe, PtCo), especially in an intermetallic L10 structure, have attracted considerable interest due to their respectable activity and stability for the oxygen reduction reaction (ORR) in proton exchange membrane fuel cells (PEMFCs). However, metal‐catalyzed formation of ·OH from H2 O2 (i.e., Fenton reaction) by Fe‐ or Co‐containing catalysts causes severe degradation of PEM/catalyst layers, hindering the prospects of commercial applications. Zinc is known as an antioxidant in Fenton reaction, but is rarely alloyed with Pt owing to its relatively negative redox potential. Here, sub‐4 nm intermetallic L10 ‐PtZn nanoparticles (NPs) are synthesized as high‐performance PEMFC cathode catalysts. In PEMFC tests, the L10 ‐PtZn cathode achieves outstanding activity (0.52 A mgPt −1 at 0.9 V iR ‐free, and peak power density of 2.00 W cm −2 ) and stability (only 16.6% loss in mass activity after 30 000 voltage cycles), exceeding the U.S. DOE 2020 targets and most of the reported ORR catalysts. Density function theory calculations reveal that biaxial strains developed upon the disorder‐order (A1L10 ) transition of PtZn NPs would modulate the surface PtPt distances and optimize PtO binding for ORR activity enhancement, while the increased vacancy formation energy of Zn atoms in an ordered structure accounts for the improved stability. Abstract : Structurally ordered L10 ‐PtZn nanoparticles are developed as catalysts for oxygen reduction in proton exchange membrane fuel cells (PEMFCs). The L10 ‐PtZn catalyst with a "Pt‐skin" achieves outstanding activity, power density, and stability in a PEMFC. The extraordinary fuel cell performance of L10 ‐PtZn/Pt is ascribed to the optimized biaxial strains, the Fenton reaction resistance, and the increased vacancy formation energy of Zn.